2023
DOI: 10.1186/s12968-023-00946-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac reverse remodeling in primary mitral regurgitation: mitral valve replacement vs. mitral valve repair

Abstract: Background When feasible, guidelines recommend mitral valve repair (MVr) over mitral valve replacement (MVR) to treat primary mitral regurgitation (MR), based upon historic outcome studies and transthoracic echocardiography (TTE) reverse remodeling studies. Cardiovascular magnetic resonance (CMR) offers reference standard biventricular assessment with superior MR quantification compared to TTE. Using serial CMR in primary MR patients, we aimed to investigate cardiac reverse remodeling and resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…Therefore, disrupting this annulo-ventricular continuity due to the (partial) removal of the subvalvular apparatus during MV replacement is hypothesized to result in less favorable post-operative LV geometry and function compared to MV repair. However, MVR with the preservation of the papillary muscles and/or chordae tendineae is associated with similar post-operative LV reverse remodeling compared to MV repair, as was recently observed by Craven et al [17]. Their findings are in line with our data and subgroup analysis excluding patients without MV subvalvular apparatus preservation, which confirmed that BD was associated with a significantly larger post-operative decrease in LVEF compared to FED.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, disrupting this annulo-ventricular continuity due to the (partial) removal of the subvalvular apparatus during MV replacement is hypothesized to result in less favorable post-operative LV geometry and function compared to MV repair. However, MVR with the preservation of the papillary muscles and/or chordae tendineae is associated with similar post-operative LV reverse remodeling compared to MV repair, as was recently observed by Craven et al [17]. Their findings are in line with our data and subgroup analysis excluding patients without MV subvalvular apparatus preservation, which confirmed that BD was associated with a significantly larger post-operative decrease in LVEF compared to FED.…”
Section: Discussionsupporting
confidence: 92%
“…However, it cannot be ascertained whether the LGE was directly related to the surgical intervention nor to the ventricular arrhythmias. Two recent prospective studies assessed LV remodeling after mitral valve surgery for primary mitral regurgitation using CMR at the 6-months follow-up [16,17]. Craven et al compared LV remodeling between mitral valve replacement (n = 30) and mitral valve repair (n = 22), but unfortunately the LGE sequences were incomplete or of insufficient quality for direct comparison [17].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent prospective studies assessed LV remodeling after mitral valve surgery for primary mitral regurgitation using CMR at the 6-months follow-up [16,17]. Craven et al compared LV remodeling between mitral valve replacement (n = 30) and mitral valve repair (n = 22), but unfortunately the LGE sequences were incomplete or of insufficient quality for direct comparison [17]. Liu et al studied 105 patients who underwent mitral valve repair and found no change in LGE before and 8.8 months after mitral valve surgery [16].…”
Section: Discussionmentioning
confidence: 99%